Horticultural performance and QTL mapping of snap bean (Phaseolus vulgaris L.) populations with organic and conventional breeding histories - Hayley E. P. Richardson; Ryan M. King; Joel Davis; James R. Myers (Frontiers in Plant Science)
IntroductionImproving crop cultivars for use on organic farms is pertinent, as current elite germplasm is less resilient within the more variable context of organic farm environments. Although a growing number of studies have focused on organic plant breeding in cereal crops, very few have focused on vegetable crops, especially those such as snap beans (Phaseolus vulgaris) that are grown for both fresh market and processing use.MethodsWe developed four populations of recombinant inbred lines under parallel organic and conventional management; utilizing these populations, we explored how historic breeding history influences the performance of snap bean progeny.ResultsWe identified significant increases in germination speed and rate, suggesting that beans bred within an organic production environment are more resilient to early-season stressors without support of chemical interventions. We also found that root branching density increased among organically-bred bean families, while root disease decreased in both the organically-bred bean families and the populations with ‘OR5630’ × ‘Black Valentine’ parentage. After developing linkage maps for each of our four populations, we identified QTL associated with days to germination, early-season vigor, root morphology, disease, days to flowering, and seed weight.DiscussionThis study lays the groundwork for improving snap bean germplasm for performance in organic systems by tracking the microevolutions created through long-term selection under organic or conventional management (i.e., breeding history). By understanding these shifts, plant breeders will begin to build a toolbox of genetic information that they can leverage in modern breeding work for organic crop cultivars.